1992
DOI: 10.1093/jmedent/29.2.259
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analysis of the Distribution of Ixodes dammini (Acari: Ixodidae) on White-Tailed Deer in Ogle County, Illinois

Abstract: The pattern of infestations of Ixodes dammini on white-tailed deer in Ogle County in Illinois was studied through examinations of hunted deer from 1988 to 1990. The Illinois Geographic Information System mapped the spatial distribution of tick infestations on deer and related it to a known endemic focus for I. dammini and Borrelia burgdorferi (Castle Rock State Park), and to a major waterway (Rock River). Second-order neighborhood analysis was used to analyze the spatial distribution of deer around Castle Rock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 0 publications
2
42
0
1
Order By: Relevance
“…33 Sandy soils have better drainage and have been associated with tick endemicity in Illinois. 19 In Wisconsin, soils of medium to fine particle size are usually saturated at the time of spring thaw 33 when adults begin questing, and tick survival may be adversely affected in soils with greater proportions of silt and clay. This study suggests that a combination of interrelated environmental factors is involved in determining the optimal habitat for I. scapularis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Sandy soils have better drainage and have been associated with tick endemicity in Illinois. 19 In Wisconsin, soils of medium to fine particle size are usually saturated at the time of spring thaw 33 when adults begin questing, and tick survival may be adversely affected in soils with greater proportions of silt and clay. This study suggests that a combination of interrelated environmental factors is involved in determining the optimal habitat for I. scapularis.…”
Section: Discussionmentioning
confidence: 99%
“…Residence in forested areas and on well-drained, deep, loamy soils were significant risk factors. 18 In Illinois, increased tick densities on white-tailed deer were found in forested areas with sandy soils near rivers, 19 and in Wisconsin, a higher incidence of human cases was seen in counties with greater forest cover. 20 In these states, populations of I. scapularis reservoir hosts, such as white-tailed deer and white-footed mice, are ubiquitous in wooded areas.…”
Section: Introductionmentioning
confidence: 99%
“…Distances where clustering occurs and where departure from randomness is most pronounced can then be identified (Getis and Franklin, 1987;Boots and Getis, 1998;O'Brien et al, 1999). Second order neighbourhood analysis was modified by Kitron et al (1992) to verify the higher degree of aggregation of tick-infested white-tailed deer around a known focus of Lyme borreliosis in northwest Illinois. In a similar approach, second order properties of the distributions of all dogs (IFA+ and IFA−) was characterised by modifying the equation for K-function as reported in Fotheringham et al (2000), to test clustering of dogs around two points (i.e.…”
Section: Spatial Analysismentioning
confidence: 99%
“…Borrelia burgdorferi, the causative agent of LD, may occur in urban and suburban development areas as well as in isolated park/forest preserves where deer, rodents, and birds can thrive [35]. Others [4] reported that I. scapularis were most abundant on sandy soils with deciduous forests.…”
Section: Discussionmentioning
confidence: 99%
“…These geospatial mapping exercises outline areas having high probabilities of vector prevalence and then infer disease risk based on probable presence or absence. For example, abundance of the tick genus Ixodes, one of which is the vector primarily responsible for the transmission of Lyme disease (LD), is associated with temperature, landscape slope [3], forested areas with sandy soils [4], and increasing residential development [5]. Tularemia prevalence is positively associated with dry forested habitat areas [6].…”
Section: Introductionmentioning
confidence: 99%